Strategi-Strategi untuk Pengajaran Konsep-Konsep Matematik - Lee , Chuan Seng (Penerbit Universiti Sains Malaysia, 1979)
This paper discusses a scheme which consists of four basic strateqies for the teaching of concepts in primary and secondary school mathematics. In th is scheme, a concept is regarded as a set of attributes that characterizes a class of objects and has a symbol or a name to denote it. The name for a concept helps to convey the set of attributes that defines the concept as an integrated whole or entity that exists independent of the class.of objects, called a reference set, from which it is abstracted. A concept may have more than one set of attributes to define it, the choice of which depend. largely on the aim of teaching the concept and the characteristics of the learners. At times, the set of attributes which defines a concept is a subset of that which defines another concept. In this case, the latter is considered of higher order than the former. On the basis of this definition of the order of concept, a hierarchy of selected concepts is built up which may offer guidance for the teaching of the related concepts. Along with the guidance of other teaching \juidelines, a set of four basic strategies are proposed and ana lysed for the teaching of mathematical concepts. They are characterization, exemplification, analogy, and symbolization. A combination of these constitutes a strategy, chosen as a result of a number of considerations, for teaching a given concept. The effectiveness of the chosen strategy will also depend on the process or method used to carrv it out in a specific teaching situation.